2003
DOI: 10.1007/s00422-002-0371-9
|View full text |Cite
|
Sign up to set email alerts
|

A coupled oscillator model of disordered interlimb coordination in patients with Parkinson's disease

Abstract: Coordination between the left and right limbs during cyclic movements, which can be characterized by the amplitude of each limb's oscillatory movement and relative phase, is impaired in patients with Parkinson's disease (PD). A pedaling exercise on an ergometer in a recent clinical study revealed several types of coordination disorder in PD patients. These include an irregular and burst-like amplitude modulation with intermittent changes in its relative phase, a typical sign of chaotic behavior in nonlinear dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 87 publications
(97 reference statements)
0
48
0
Order By: Relevance
“…In addition, neurophysiological modeling studies have shown that salient stability-related phenomena in interlimb coordination (e.g., in-phase being more stable than antiphase; frequency-induced transitions between movement patterns) can arise in a system of two coupled neural oscillators in the absence of afferent feedback, yielding a dynamical account of integrated timing (Asai et al 2003;Grossberg et al 1997). However, afference-based interlimb interactions have also been demonstrated, e.g., in the form of effects of passive limb movements on the stability of rhythmic interlimb coordination (Serrien et al 2001;Stinear and Byblow 2001;Swinnen et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, neurophysiological modeling studies have shown that salient stability-related phenomena in interlimb coordination (e.g., in-phase being more stable than antiphase; frequency-induced transitions between movement patterns) can arise in a system of two coupled neural oscillators in the absence of afferent feedback, yielding a dynamical account of integrated timing (Asai et al 2003;Grossberg et al 1997). However, afference-based interlimb interactions have also been demonstrated, e.g., in the form of effects of passive limb movements on the stability of rhythmic interlimb coordination (Serrien et al 2001;Stinear and Byblow 2001;Swinnen et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Characteristic wave forms for cluster 1 or 2 showed relatively preserved pattern of interlimb coordination that was characterized by coordinative movements of right and left pedals, while those for cluster 3 or 4 showed impaired pattern of interlimb coordination [3][4][5] . Six patients with parkinsonism classified into cluster 3 or 4.…”
Section: Discussionmentioning
confidence: 96%
“…These patterns, which included irregular and burst-like amplitude modulations with intermittent changes in the relative phase, correlated with the presence of the freezing phenomenon in patients with patients with parkinsonism. Asai et al suggested that these particular amplitude modulations could be viewed as a typical sign of chaotic behavior in nonlinear dynamical systems 3) . These may be characteristic features of interlimb coordination.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Calancie [9] and Dimitrijevic et al [10] described the performance of rhythmic movements when electric stimulation was applied to spinal cord injury victims at constant intervals. Against this background, rhythmic movements such as walking have been modeled based on a CPG [11], [12]. It should be noted that CPG models cannot express non-stationary features of movements such as rapid changes in rhythm, amplitude and velocity even if the relevant structure can be determined appropriately.…”
Section: Introductionmentioning
confidence: 99%